‘Tecnologia social’ and social change: the case of Agência de Redes in Rio de Janeiro - Saldanha, Fabio Prado; Aguilar-Delgado, Natalia; Pozzebon, Marlei (Revista Brasileira de Casos de Ensino em Administração, 2019)
The case provides an opportunity to understand how tecnologia social – a South American concept that might be seen as an equivalent to social innovation – can help promote social change. To illustrate the potential of social technologies, the case of Agência de Redes is presented. The case is intended for use at both the undergraduate and graduate levels. Its purpose is to promote the discussion of the South American concept of tecnologia social, as well as to analyse of one particular tecnologia social using a conceptual model to understand the mechanisms that might promote social change.